Effect of hope therapy on the mood status of patients with diabetes - Firouz KhalediSardashti; Zahra Ghazavi; Farshad Keshani; Mojtaba Smaeilzadeh (Wolters Kluwer Medknow Publications, 2018)
Background: Diabetes mellitus (DM) is a chronic disease which imposes high costs on patients and society and results in complications in patients. One of these complications includes issues related to mood. Thus, the present study was conducted with the aim to determine the effect of hope therapy on the mood status of patients with DM. Materials and Methods: This quasi-experimental study was performed with two groups in three stages in the summer of 2015 on 38 individuals. The study population consisted of all individuals with DM who referred to and had a medical record at Shahid Asghar Shabani Clinic (Isfahan, Iran) affiliated with the social security organization. From among the 350 individuals with medical records at the clinic, 38 who had the inclusion criteria were selected through simple random sampling. Participants were randomly assigned to control (n = 19) and experimental (n = 19) groups. The Zung Self-Rating Depression Scale was completed by both groups before, after, and 1 month after the intervention. Results: There was a significant difference in the mean scores of depression in the intervention group before (F = 19.48, p = 0.001), immediately after (t = 3.30, p = 0.002), and 1 month after the intervention (t = 3.09, p = 0.004), whereas there was no significant difference in the mean scores of depression before, immediately after, and 1 month after the intervention in the control group. Conclusions: The obtained results showed that hope therapy can reduce depression in patients with DM.